Faktor-Faktor Yang Mempengaruhi Penggunaan Media Sosial Instagram Terhadap Kepuasan Pengusaha Wanita - Vanessya Blandina Dasmasela; Hetty Karunia Tunjungsari (Jurnal Manajerial Dan Kewirausahaan, 2021)
The purpose of this study was to determine and analyze the factors that influence the use of social media Instagram and its impact on the satisfaction of women entrepreneurs. This research was conducted by using judgment sampling method. Researchers distributed questionnaires to 200 women entrepreneurs. Data analysis using PLS SEM analysis. The results of the analysis conclude that Multi-channel has a significant effect on the use of social media among women entrepreneurs in West Jakarta. Trust has a significant effect on the use of social media among women entrepreneurs in West Jakarta. Ease has no significant effect on the use of social media among women entrepreneurs in West Jakarta. Accessibility has a significant effect on the use of social media among women entrepreneurs in West Jakarta. Security has a significant effect on the use of social media among female entrepreneurs in West Jakarta. Benefits have a significant effect on the use of social media among women entrepreneurs in West Jakarta. The use of social media has a significant effect on the satisfaction of women entrepreneurs in West Jakarta. The use of social media is able to mediate the effect of multi-channel on the satisfaction of entrepreneurs in West Jakarta. The use of social media is able to mediate the effect of trust on entrepreneur satisfaction in West Jakarta. The use of social media is not able to mediate the effect of convenience on the satisfaction of entrepreneurs in West Jakarta. The use of social media is able to mediate the effect of accessibility on entrepreneur satisfaction in West Jakarta. The use of social media is able to mediate the effect of security on the satisfaction of entrepreneurs in West Jakarta. The use of social media is able to mediate the effect of benefits on entrepreneur satisfaction in West Jakarta Tujuan penelitian ini adalah untuk mengetahui dan menganalisa faktor-faktor yang mempengaruhi penggunaan media sosial instagram dan dampaknya terhadap kepuasan pengusaha wanita. Penelitian ini dilakukan dengan metode judgement sampling. Peneliti menyebarkan kuesioner kepada 200 pengusaha wanita. Analsisi data menggunakan analisis SEM PLS. Hasil analisis menyimpulkan bahwa Multi-channel berpengaruh signifikan terhadap penggunaan media sosial di kalangan pengusaha wanita di Jakarta Barat. Kepercayaan berpengaruh signifikan terhadap penggunaan media sosial di kalangan pengusaha wanita di Jakarta Barat. Kemudahan tidak berpengaruh signifikan terhadap penggunaan media sosial di kalangan pengusaha wanita di Jakarta Barat. Aksesibility berpengaruh signifikan terhadap penggunaan media sosial di kalangan pengusaha wanita di Jakarta Barat. Keamanan berpengaruh signifikan terhadap penggunaan media sosial di kalangan pengusaha wanita di Jakarta Barat. Manfaat berpengaruh signifikan terhadap penggunaan media sosial di kalangan pengusaha wanita di Jakarta Barat. Penggunaan media sosial berpengaruh signifikan terhadap kepuasan pengusaha wanita di Jakarta Barat. Penggunaan media sosial mampu memediasi pengaruh multi-channel terhadap kepuasan pengusaha di Jakarta Barat. Penggunaan media sosial mampu memediasi pengaruh kepercayaan terhadap kepuasan pengusaha di Jakarta Barat. Penggunaan media sosial tidak mampu memediasi pengaruh kemudahan terhadap kepuasan pengusaha di Jakarta Barat. Penggunaan media sosial mampu memediasi pengaruh aksesibility terhadap kepuasan pengusaha di Jakarta Barat. Penggunaan media sosial mampu memediasi pengaruh keamanan terhadap kepuasan pengusaha di Jakarta Barat. Penggunaan media sosial mampu memediasi pengaruh manfaat terhadap kepuasan pengusaha di Jakarta Barat